Blind pouch syndrome: Case report and literature review - Corleta, Oly; Moschetti, Laura; Basso Dias, Adriano; de Araújo, Guilherme (Clinical and Biomedical Research, 2015)
Blind pouch syndrome is the set of signs and symptoms caused by intestinal content stasis and consequent bacterial hyperproliferation in a segment excluded from the intestinal flow after surgical procedure. This paper reports the case of a 65-year-old male patient complaining of diffuse abdominal pain, poor oral intake, nausea, diarrhea, fever and chills. Surgical history included cecal resection five years before due to a tubulovillous adenoma. On physical examination, the abdomen was tender and distended, without signs of peritonitis. Complete blood cells count showed microcytic anemia. Computed tomography of the abdomen revealed ileocolonic anastomosis (ascending) with blind loop presenting signs of inflammatory process. Exploratory laparotomy was indicated, in which the resection of the blind loop was performed. After gradual improvement of the symptoms, the patient was discharged in12th post-operative day.